2023
DOI: 10.3390/cancers15194766
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of M1 Muscarinic Receptors Attenuates Human Colon Cancer Cell Proliferation

Margaret H. Sundel,
Natalia Sampaio Moura,
Kunrong Cheng
et al.

Abstract: M3 muscarinic receptor (M3R) activation stimulates colon cancer cell proliferation, migration, and invasion; M3R expression is augmented in colon cancer and ablating M3R expression in mice attenuates colon neoplasia. Several lines of investigation suggest that in contrast to these pro-neoplastic effects of M3R, M1R plays an opposite role, protecting colon epithelial cells against neoplastic transformation. To pursue these intriguing findings, we examined the relative expression of M1R versus M3R in progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 44 publications
(67 reference statements)
0
0
0
Order By: Relevance
“…In vitro, McN-A-343 and xanomeline dose-dependently inhibited colon cancer cell proliferation, an effect reversed by pre-treating cells with a selective M 1 R inhibitor [163]. Moreover, adding McN-A-343 to standard colon cancer chemotherapy, namely 5-fluorouracil and oxaliplatin, potentiated their anti-proliferative effects on colon cancer cells [163].…”
Section: Subtype-selective Muscarinic Receptor Agonists or Antagonistsmentioning
confidence: 95%
See 4 more Smart Citations
“…In vitro, McN-A-343 and xanomeline dose-dependently inhibited colon cancer cell proliferation, an effect reversed by pre-treating cells with a selective M 1 R inhibitor [163]. Moreover, adding McN-A-343 to standard colon cancer chemotherapy, namely 5-fluorouracil and oxaliplatin, potentiated their anti-proliferative effects on colon cancer cells [163].…”
Section: Subtype-selective Muscarinic Receptor Agonists or Antagonistsmentioning
confidence: 95%
“…M 3 R blockade in human colon cancer cell lines counteracted ACh-induced ERK1/2, Akt, and MMP-1 signaling, consequently attenuating cell proliferation and invasion [149]. Further, M 1 R expression is downregulated in human CRC tissue and may protect colon cells against neoplastic transformation [163]. In human colon cancer cell lines, Sundel et al demonstrated that M 1 R agonism inhibits cell proliferation and augments the effects of conventional chemotherapeutic agents [163].…”
Section: Colorectal Cancermentioning
confidence: 99%
See 3 more Smart Citations